2019
DOI: 10.7150/jca.31660
|View full text |Cite
|
Sign up to set email alerts
|

The difference in prognosis of stage II and III colorectal cancer based on preoperative serum tumor markers

Abstract: Background : Preoperative serum tumor markers have been widely used to predict prognosis in stage II and III colorectal cancer (CRC). However, few previous studies addressed the effect of increased preoperative numbers of tumor markers. Methods : Patients with stage II and III CRC who underwent curative resection were included from January 2009 to October 2015. The relationship between serum tumor markers and clinicopathological parameters was analyzed. DFS and OS were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
(30 reference statements)
3
21
0
Order By: Relevance
“…Moreover, many studies have demonstrated that CA242 works well in predicting the diagnosis, progression, and prognosis of colorectal cancer in combination with other tumor markers [18,19,26,30]. Our results showed that the mean value in colorectal cancer was 26.50±59.58 and that the AUC was 0.7241 (0.7073, 0.7408) ( Table 1), which was consistent with previous studies [22,26,27].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, many studies have demonstrated that CA242 works well in predicting the diagnosis, progression, and prognosis of colorectal cancer in combination with other tumor markers [18,19,26,30]. Our results showed that the mean value in colorectal cancer was 26.50±59.58 and that the AUC was 0.7241 (0.7073, 0.7408) ( Table 1), which was consistent with previous studies [22,26,27].…”
Section: Discussionsupporting
confidence: 91%
“…CA242 has been reported to be more sensitive and speci c than CA50 and CEA in Dukes' A-D colorectal cancer [22], in addition to its considerable value in predicting recurrence and metastasis in clinical stage II and III colorectal cancer [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in clinical practice, should we refer to the levels of perioperative serum CEA when we give patients treatment recommendations? In addition, we also found that the number of preoperative elevated tumor markers also had important impact on the prognosis of CRC, including CEA, CA19-9, CA242, and CA125 (28). We believe that serum tumor markers have great value in CRC, but these markers have not been paid enough attention in the clinic.…”
Section: Discussionmentioning
confidence: 93%
“…CA242 has been reported to be more sensitive and speci c than CA50 and CEA in Dukes' A-D colorectal cancer [22], in addition to its considerable value in predicting recurrence and metastasis in clinical stage II and III colorectal cancer [18]. Moreover, many studies have demonstrated that CA242 works well in predicting the diagnosis, progression, and prognosis of colorectal cancer in combination with other tumor markers [18,19,26,30]. Our results showed that the mean value in colorectal cancer was 26.50 ± 59.58 and that the AUC was 0.7241 (0.7073, 0.7408) (Table 1), which was consistent with previous studies [22,26,27].…”
Section: Page 14/19mentioning
confidence: 99%